European Society of Pediatric Nephrology survey on current practice regarding recurrent focal segmental glomerulosclerosis after pediatric kidney transplantation - Bouts, Antonia; Tönshoff, Burkhard (Pediatric transplantation, 2019)
Introduction Primary FSGS is an important cause of ESRD in children. FSGS recurrence after kidney transplantation is associated with early graft loss. No guidelines for treatment of FSGS recurrence exist. We conducted a survey to gain insight into variation of treatment between centers. Methods A survey was sent to all members of the ESPN on behalf of the “Renal Transplantation” and “Idiopathic Nephrotic Syndrome” working groups. Results Fifty-nine nephrologists from 31 countries responded, reporting 807 FSGS patients, with 241 (30%) FSGS recurrences after transplantation. Recurrence varied from 0% to 100% between respondents. Native nephrectomy before or during transplantation was performed, respectively, always (37%), never (39%), or on clinical indication (17%). Half of the respondents started preventive treatment before transplantation, using PF (n = 10); R (n = 4); PF or IA, plus R (n = 9); cyclosporine (n = 2); or unknown (n = 4). Immunosuppressive therapy for patients without known mutations consisted of a combination of steroids, tacrolimus/cyclosporine, and MMF, with or without IL-2R-blockade in, respectively, 61% and 86% of the respondents. Sixty-three percent applied a similar regimen to patients with known mutations. FSGS recurrence was treated with PF or IA, plus R by 66% of respondents; 54% observed no response. Complete remission in >50% of patients was reported by 41% of the respondents. Discussion FSGS recurrence after transplantation is common, but varies greatly between centers. We found great variability in preventive and therapeutic treatment regimens. Future research should focus on predisposing factors, including biopsy findings and genetic mutations, and standardized treatment.
Gesehen am 10.09.2019